PARIWISATA HALAL MENURUT PANDANGAN AL-QUR’AN - Hutagaluh, Oskar; Abubakar, Achmad; Haddade, Hasyim (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
This research is based on the clues in the verses of the Koran related to tourism activities. Tourism in Islam is related to trip or travel undertaken by a person, both individually and as a group to go to some area. However, the paradigm of tourism so far is aimed at momentary pleasure, with hedonistic values ​​so that tourism turns into halal tourism. This study aims to describe the verses of the Koran which have messages for the people regarding halal tourism activities. This research approach is qualitative with the data sources are from various literatures. Based on this research, it is found that the verses of the Koran have provided a basis for halal tourism such as traveling together, enjoying God's creation, consuming halal food, and conducting sharia transactions, as well as sharia-compliant tourism activities.